2014
DOI: 10.1038/bcj.2014.67
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and intratumoral heterogeneity of BCL2 correlates with IgH expression and prognosis in follicular lymphoma

Abstract: Most follicular lymphomas (FLs) are genetically defined by the t(14;18)(q32;q21) translocation that juxtaposes the BCL2 gene to the immunoglobulin heavy chain (IgH) 3' regulatory regions (IgH-3'RRs). Despite this recurrent translocation, FL cases are heterogeneous in terms of intratumoral clonal diversity for acquired mutations and variations in the tumor microenvironment. Here we describe an additional mechanism that contributes to inter- and intratumoral heterogeneity in FLs. By applying a novel single-molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 43 publications
2
12
1
Order By: Relevance
“…Findings suggestive of the latter were observed in several types of tumor, such as breast cancer, head and neck squamous cell carcinoma, and primary rectal cancer . In lymphomas, there is an additional, strong heterogeneity in NHL due to the considerable number of histological subtypes, which further increases the tumor tissue heterogeneity between patients, adds to the biological complexity, and may be chiefly responsible for the variability detected in our study, as well as in previous studies …”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Findings suggestive of the latter were observed in several types of tumor, such as breast cancer, head and neck squamous cell carcinoma, and primary rectal cancer . In lymphomas, there is an additional, strong heterogeneity in NHL due to the considerable number of histological subtypes, which further increases the tumor tissue heterogeneity between patients, adds to the biological complexity, and may be chiefly responsible for the variability detected in our study, as well as in previous studies …”
Section: Discussionsupporting
confidence: 80%
“…Findings suggestive of the latter were observed in several types of tumor, such as breast cancer, head and neck squamous cell carcinoma, and primary rectal cancer. [8][9][10][11][12] In lymphomas, there is an additional, strong heterogeneity in NHL due to the considerable number of histological subtypes, [33][34][35][36] which further increases the tumor tissue heterogeneity between patients, adds to the biological complexity, and may be chiefly responsible for the variability detected in our study, as well as in previous studies. 3,15,16,19,25,37 Moreover, the quantitative ADC and SUV data are also influenced by several technical factors, such as the selection of the b-values, acquisition technique (EPI-SPAIR or STIR-based; free-breathing, breath-hold, or respiratory triggered), and the presence of artifacts for DWI.…”
Section: Discussionsupporting
confidence: 54%
“…By taking note of the nonequilibrium percentages of tumor cells and the different cytogenetic aberrations involved, ITH can be analyzed using FISH, which was utilized in this study as reported previously. 30,31 In this study, we found that two genetic subclones could be distinguished in the presence of two or more aberrations detected by FISH. In patients with unfavorable clones (i.e., containing del 11q/del 17p), three genetic subclones could be defined.…”
Section: Discussionmentioning
confidence: 54%
“…Within a tumor, there may be great variability among cells in the levels of pro- and anti-apoptotic factors, with certain clones being more apoptosis reluctant than others. In support of this notion, it was recently discovered that extensive intratumor heterogeneity exists in Bcl-2 transcript levels in follicular lymphoma as assessed at the single-cell level [22]. Patient-derived lymphoma cells that expressed higher levels of Bcl-2 were more resistant to the cytotoxin doxorubicin.…”
Section: The Road Forward: Studying and Combating Heterogeneity In Apopmentioning
confidence: 99%